2016
DOI: 10.3892/ijo.2016.3786
|View full text |Cite
|
Sign up to set email alerts
|

Differential detection of cytoplasmic Wilms tumor 1 expression by immunohistochemistry, western blotting and mRNA quantification

Abstract: Abstract. Wilms tumor 1 (WT1) is considered to be a promising target of cancer treatment because it has been reported to be frequently expressed at high levels in various malignancies. Although WT1-targeted cancer treatment has been initiated, conclusive detection methods for WT1 are not established. The present study aimed to consolidate immunohistochemistry for WT1 with statistical basis. Transfected cells with forced WT1 expression yielded specific western blot bands and nuclear immunostaining; cytoplasmic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
8
1
Order By: Relevance
“…Unlike other tumor suppressor genes, WT1 appears to be expressed in selected mesoderm‐derived cell types, such as the mesothelium, kidney, and gonads . In humans, WT1 is considered a useful mesothelial marker, with positive rates of 100% for reactive mesothelium and between 72% and 100% of mesotheliomas . In our CTB case series and the validation study, WT1 stained positively for all cases of normal, reactive mesothelium, and mesotheliomas (including cases negative for vimentin).…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…Unlike other tumor suppressor genes, WT1 appears to be expressed in selected mesoderm‐derived cell types, such as the mesothelium, kidney, and gonads . In humans, WT1 is considered a useful mesothelial marker, with positive rates of 100% for reactive mesothelium and between 72% and 100% of mesotheliomas . In our CTB case series and the validation study, WT1 stained positively for all cases of normal, reactive mesothelium, and mesotheliomas (including cases negative for vimentin).…”
Section: Discussionmentioning
confidence: 67%
“…Several monoclonal and polyclonal antibodies against WT1 are available with different recognition sites along the amino acid sequence . Recently, it was reported that monoclonal antibodies (and particularly the clone used herein) that stain the entire nucleus correlated with Western blot band intensities and mRNA expression levels . In contrast, no correlation was observed with cytoplasmic immunostaining (regardless of which antibody was used) and was considered as nonspecific finding .…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations